Barriers and affordances teachers encounter when teaching mathematics for social justice : I get it now it's racism : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Albany, New Zealand - Bills, Trevor (Massey University, 2020)
This study examines the barriers and affordances teachers encounter when implementing a critical pedagogical approach to mathematics as well as looking at the support teachers require overcoming these barriers. In doing so, it questions if mathematics education can be re-imagined to not only meet the vision of the New Zealand Curriculum but also to create a socially just world. It builds on previous work in critical mathematics education involving culturally sustaining mathematics pedagogy and teaching mathematics for social justice. The study applied a Freirean perspective to the teaching of mathematics. Freire asserts that in order to be transformative pedagogy must be forged with, not for the oppressed. Oppression and its causes need to become objects of reflection as from this reflection comes the necessary engagement for liberation. The investigation took place in an inquiry-based mathematics community involving six teachers working in an innovative learning environment. Four of the teachers were Pāsifika, one was Māori and the other Pākehā. The students were predominantly Pāsifika. The teachers in the study were supported to problematize the students’ world by providing mathematical tasks that examined inequity in New Zealand society. The intention was that this would challenge students to move towards a self- construction of their world based on rationality and reason that could lead to praxis or informed action. The challenges teachers faced in achieving this were then examined along with the pedagogical actions they took to move past these challenges. A qualitative approach applying an interpretivist paradigm underpinned this study. A narrative inquiry process based on Talanoa allowed the participants voices to be heard and their story to be told. Data was gathered using an initial questionnaire and then through ongoing open-ended interviews as well as video-recorded observations and classroom artefacts. The findings indicate that the teachers went into the study with a narrow view of what teaching mathematics for social justice involved but through reflection and ongoing Talanoa this evolved over time to incorporate the inclusive, culturally sustaining pedagogical actions that they had previously been doing. The study also found that many of the external barriers they thought they would encounter did not eventuate and that the main (and largely unanticipated) challenge would come from the students’ internalised oppression. The studies exposure of that internalised oppression however, afforded the teachers the opportunity to confront the deficit thinking of their students and in turn confront their own beliefs about teaching mathematics. The investigation illustrated that teacher empowerment through reflection was related to the empowerment of their students and presented the possibility of liberation for both.
Keywords: 390109 Mathematics and numeracy curriculum and pedagogy; 390203 Sociology of education